Vision Related Quality of Life in Patients with Keratoconus - Sevda Aydin Kurna; Ahmet Altun; Tugba Gencaga; Sezen Akkaya; Tomris Sengor (Journal of Ophthalmology)
Purpose. The purpose of this study is to evaluate the vision related quality of life in patients with keratoconus by using the National Eye Institute Visual Function Questionnaire-25 (NEI-VFQ-25). Methods. Thirty patients presented with keratoconus (keratoconus group) and 30 healthy patients (control group) were included in this study. Twenty patients were using rigid gas permeable and 10 patients were not using contact lenses in keratoconus group. High and low contrast visual acuity and mean K values of the patients were recorded. Each subject completed the 25-item NEI-VFQ-25. Results. All subscales of NEI-VFQ-25 were lower in the keratoconus patients. The difference was more evident in the subscales of general vision, ocular pain, near vision, vision-specific mental health, vision-specific role difficulties, and peripheral vision P<0.05. Overall composite score was 75.2 ± 17.2 in the keratoconus group and 93.2 ± 5.6 in the control group P=0.00. Contact lens wearers had higher best corrected visual acuity in comparison with noncontact lens wearers P=0.028. Patients with low visual acuity (logMAR > 0.4) in the better eye had lower distance vision, social functioning, mental health, and role difficulties. Meanwhile, patients with low visual acuity (logMAR > 0.4) in the worse eye had lower general health scores P<0.05. Conclusions. Vision related quality of life was worse in keratoconus patients. Success in the contact lens usage and maintaining higher visual acuity may improve vision related quality of life.